Integrating Local Wisdom into Disaster Mitigation Education to Improve the Understanding of Disasters - Linda Dwi Astuti; Aulia Silvina Anandita (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Indonesia has a high level of disaster vulnerability, so it is necessary to strengthen the understanding of disasters through higher education. This study aims to analyze the improvement of students' understanding of disasters through local wisdom-based learning in the Introduction to Earth Science and Disaster Mitigation course. The study used a descriptive quantitative approach with a one-group pretest-posttest design. The research subjects were students of the Physics Education Program in the second semester of 2024/2025. The instrument was a multiple-choice test covering three aspects: conceptual understanding of disasters, understanding of local wisdom, and application of knowledge in daily life. Data were analyzed using a paired sample t-test and N-Gain. The results showed a significant increase in all three aspects. Conceptual understanding increased from 70.34 to 85.05 (N-Gain = 0.50), understanding of local wisdom increased from 63.18 to 87.58 (N-Gain = 0.66), and application of knowledge in real life increased from 71.32 to 92.40 (N-Gain = 0.74). These results indicate that local wisdom-based learning is effective in strengthening students' scientific and contextual understanding of disasters, with moderate to high effectiveness based on N-Gain analysis. This approach is relevant for sustainable application in higher education to build preparedness and awareness of disaster risks.